2015
DOI: 10.1021/acs.joc.5b00411
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-Catalyzed β-Carboline Directed C–H Arylation and Isolation of Its Cycloruthenated Intermediates

Abstract: A Ru(II)-catalyzed C-H arylation approach has been developed utilizing β-carboline alkaloids as the directing group. Selective formations of diarylated products from moderate to excellent yields were accomplished. Broad substrate scope with excellent functional group tolerance for C1-phenyl/thienyl/PAHs-β-carbolines was demonstrated. X-ray crystal structure of cycloruthenated complex 2cr and no arylation reaction with model substrate 13 strongly suggests that N2 is the directing group than N9 in C1-aryl-β-carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Literature review shows that β‐carboline directed C–H arylation was achieved using a commercially available catalyst, dichloro( p ‐cymene) ruthenium(II) dimer complex, wherein various aryl rings were introduced . Hence, the present Ru(II)‐ p ‐cymene complexes, which are structurally different from the commercially available Ru(II) catalyst, were employed for the β‐carboline directed C–H arylation as shown in scheme .…”
Section: Catalytic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature review shows that β‐carboline directed C–H arylation was achieved using a commercially available catalyst, dichloro( p ‐cymene) ruthenium(II) dimer complex, wherein various aryl rings were introduced . Hence, the present Ru(II)‐ p ‐cymene complexes, which are structurally different from the commercially available Ru(II) catalyst, were employed for the β‐carboline directed C–H arylation as shown in scheme .…”
Section: Catalytic Evaluationmentioning
confidence: 99%
“…In the regard of catalytic applications, [Ru( η 6 ‐ p‐ cymene)(κ 2 ‐ N , N ‐dmbpy)Cl] + , where dmbpy is 4,4′‐dimethyl‐2,2′‐bipyridine is reported for its catalytic transfer hydrogenation of different ketones to the corresponding alcohols . Dichloro( p ‐cymene) ruthenium(II) dimer complex is employed as a catalyst for β‐carboline directed C–H arylation wherein various aryl ring was introduced through C‐H activation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Carboline, a privileged scaffold, is core unit of several natural alkaloids and bioactive compounds endowed with diverse pharmacological properties. 18 The first example of β-carbolinedirected ruthenium-catalyzed arylation was reported by Gandhi et al 19 Subsequently we reported Pd(OAc) 2 -catalysed regioselective alkoxylation (C-O bond formation) of aryl (βcarbolin-1-yl) methanones employing β-carboline directed ortho-C(sp2)-H activation of an aryl ring under oxidative conditions. 20 Continuing with our efforts to study the scope of β-carboline directed C(sp2)-H activation for installing various functional groups, we now disclose a Pd-catalysed β-carboline directed decarboxylative acylation using α-oxocarboxylic acid as the acyl ion source to form (2-aroylaryl) (β-carbolin-2yl)methanones.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the alkoxy unit could be readily installed via palladium-catalysed ligand assisted activation of orthoaromatic C(sp2)-H in aryl (9H-pyrido[3,4-b]indol-1yl)methanone which are readily accessible using literature procedure. 25 They demonstrated that the pyridine nitrogen of the β-carboline is responsible for the chelation with Ru leading to ortho-Caryl-H functionalization. Only very recently Gandhi et al reported Ru(II)-catalyzed C−H arylaƟon for arylating (hetero)aryl and polyaromatic hydrocarbons attached to the β-carboline scaffold utilizing β-carboline as the directing group.…”
Section: Introductionmentioning
confidence: 99%